PEMBERDAYAAN MASYARAKAT BERBASIS BUDIDAYA DALAM MENGEMBANGKAN KAMPUNG LELE DI DESA TEGALREJO KECAMATAN SAWIT KABUPATEN BOYOLALI - Arifia Anindita Kusumastuti; Achmad Taufik (Journal of Politic and Government Studies, 2020)
Poverty in Indonesia is one of the complex problems which seems to be the cause ofother problems. One way to tackle poverty is through community empowerment. Communityempowerment is a development process where the community takes the initiative to start theprocess of social activities to improve the situation and condition of oneself. The problemraised in this study is Cultivation Based Community Empowerment in Developing CatfishVillage in Tegalrejo Village, Sawit District, Boyolali Regency.The purpose of this research is to find out how the process of empowering thecommunity based on cultivation in developing the Catfish Village in Tegalrejo Village, SawitDistrict, Boyolali Regency. The method used in this research is descriptive qualitative methodby conducting data collection techniques such as interviews, observation and documentation.The informants in the study were the chairperson of the Karya Mina Utama group, the chair ofthe Karmina group, business actors, the Community Empowerment Office and the BoyolaliDistrict Village.The results of this study indicate that community empowerment that takes place isbased on three empowerment approaches, namely participatory approach which is carried outby increasing competence through training and outreach related to the fish cultivation process,sustainability approach which is carried out through institutional development empowermentactivities with the formation of Karya Mina Utama cultivators and sub-groups Karminaprocessing group, as well as environmental development activities through management ofpond control as a medium for fish cultivation, welfare approach carried out through businessdevelopment empowerment activities where through this activity the community has additionalincome from the fisheries sector.Lele Village as a cultivation-based community empowerment media is expected to bemanaged by Village-Owned Enterprises (BUMDES), so that the presence of BUMDES ownedby Lele Village can increase the existence and local potential that they have. The Departmentof Animal Husbandry and Fisheries is expected to be able to provide solutions to problemsfaced by catfish farmers, namely the limited local catfish seeds originating from BoyolaliRegency.Keywords : Empowerment, Cultivation, Village Catfish